(untitled) (Medical Forum Monthly, 2021)
Objective: To assess the knowledge, attitude and practice of Health Care Providers (HCP) regarding antenatal exercises in Pakistan. Study Design: Cross sectional study Place and Duration of Study: This study was conducted at the Sobhraj Maternity Home, Karachi from January till April 2020. Materials and Methods: A convenience sample of 152 HCP was taken. Informed consent was obtained. A goggle survey was conducted along with physical survey for this study. Practitioners who participated, obstetricians n= 65(42.8%), gynecologist n=44(28.9%) and remaining n= 43(28.3 %) general practitioners filled a questionnaire. For every response descriptive statistics were computed. Results: Most of the practitioners (97%) believed the beneficence of exercise during pregnancy however only 25.7% were found to have an adequate knowledge regarding benefits of exercise during pregnancy. In addition to it 65% of them believe that pregnant woman should be provided with the advice regarding exercise in any form such as verbal or pamphlets during antenatal visits. Majority of the practitioners (72%) were found to be unaware of the recommendations by international organizations. Conclusion: Since there seems to have a mismatch in knowledge and practice of HCP in this regard, all possible efforts should be taken for exercise promotion in pregnancy to ensure healthy mother and baby.